Taxonomic record and distribution pattern of the banded pond snail, Bellamya bengalensis (Lamarck) (Gastropoda : Mesogastropoda) from pond water habitat of Rajshahi (Bangladesh Journal of Scientific and Industrial Research, 2013)
The study was conducted on the taxonomic record and distribution pattern of the banded pond snail, Bellamya bengalensis (Lamarck ) from the water body of Rajshahi University Campus during the period of January 1995 to December 1996. Eleven generic and 18 species names were recorded including the valid name, Bellamya bengalensis (Lamarck, 1882 ). The shell of B. bengalensis is more or less oval and acuminate with variable and irregular dark bands. The snail was usually found in the littoral zone of the ponds or tanks.This snail was located in the soft or clayey bottom of the pond DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15416 Bangladesh J. Sci. Ind. Res. 48(1), 71-74, 2013